Faktor-faktor yang Mempengaruhi Kejadian Infeksi pada Pasien dengan Water Seal Drainage di RSUD Dr. Soetomo Surabaya - Farida, Imroatul; Ernita Flora; Bahtyar Hardyansyah Syihab (Gayaku Publisher, 2025)
Infection in patients with Water Seal Drainage (WSD) is a serious clinical issue that can increase both morbidity and mortality. This study aims to identify the demographic and clinical factors that influence the incidence of infection in patients with WSD at Dr. Soetomo General Hospital, Surabaya. The objectives include identifying relevant demographic and clinical factors, analyzing their relationship with infection occurrence, and providing recommendations to improve the quality of care. This research uses a cross-sectional approach with purposive sampling. Data were collected from 24 respondents using WSD and analyzed through univariate and bivariate statistics using the Spearman Rho test. The results showed that of the 24 respondents, 70.8% were male and 87.5% were married. The majority were between 45–64 years old (45.8%), and 62.5% had a low body mass index. Systemic infection was the most common type observed (45.8%). Factors such as age, duration of WSD placement, leukocyte count, and comorbidities were significantly associated with the incidence of infection. In conclusion, age, duration of WSD placement, leukocyte levels, and comorbid conditions were found to influence infection rates among WSD patients. Recommendations are made to enhance care quality and reduce the risk of infection for patients undergoing WSD at Dr. Soetomo General Hospital, Surabaya.